THE FACTORS ANALYSIS INFLUENCING TAX PAYMENTS USING E-FILLING SYSTEM (A Case Study of Lecturer and Academic Staff in Economics and Bisnis, UniversitasBrawijaya) - Ayuningtyas, Annisa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this study is to examine the factors that influence userâ€™s interest in using e-filling system service. This research was conducted in Faculty of Economics and Business UniversitasBrawijaya Malang by using survey method. Researchers obtained 101 response from the lecturer and academic staff of Accounting Department using e-filling service. The data was analyzed using SPSS model for Statistical Package for the Social Sciences. This study is quantitative research to provide more detailed information about the problems occurred in the application of information technology (e-system) in tax compliance. The results indicate that the perception of security has a negative effect, while the perception of ease and perception of ease of use have a positive and significant effect on the interest in using e-filling service.Â Keywords: Tax, E-Filling System, E-Service.